PENINGKATAN PENGETAHUAN DAN KETERAMPILAN SADARI PADA IBU USIA REPRODUKSI DI LEBAK BANDUNG TAHUN 2017 - Gustina Gustina; Nurbaiti Nurbaiti (Jurnal Abdimas Kesehatan (JAK), 2019)
Breast cancer is cancer that forms in the breast tissue. breast cancer malignancy in Indonesia. One of the ways to reduce the possibility of developing breast cancer is by stitching the breast self examination (BSE). The role of biadan can provide counseling and counseling to the public about BSE health.The community service was carried out aimed at increasing the knowledge and skills of BSE in reproductive age mothers in Bandung. This service was carried out on June 8, 2017. The community service implementation team was carried out by STIKBA lecturers about self breast examination (BSE). Dilebak bandung.